KI HADJAR DEWANTARA PELOPOR PENDIDIKAN NASIONAL - Made Suastika, Made Suastika; Nym. Kutha Ratna, Nym. Kutha Ratna; Ketut Ardhana, Ketut Ardhana (LPMPP Universitas Negeri Yogyakarta, 2002)
As a national hero,Ki Hajar Dewantara has contributedto many fields suchas culture, education, the state system,politics, and art. The changeshe has made on his name fromRaden Mas Suwardi Suryaningrat into Suwardi Suryaningrat andfinally intoKi Hajar Dewantara shows how greatly he hassacrificed in his struggle for his country's independence anddevelopment.Particularlyin the educational field, through Taman Siswa,Ki Hajar Dewantara has given very great contributions to thedevelopment ofIndonesian human resources. Hehas implantedas an investment the basic characteristics of modem educationthat he has unearthed from the treasuryof his country's tradi. tions in combination with methods and theories originating.abroad. The conceptions made through Taman Siswaare ofgreatuse in anticipating the country's mental degradation and nationaldisintegration.